Cell Cycle Inhibition without Disruption of Neurogenesis Is a Strategy for Treatment of Aberrant Cell Cycle Diseases: An Update - Da-Zhi Liu; Bradley P. Ander (The Scientific World Journal)
Since publishing our earlier report describing a strategy for the treatment of central nervous system (CNS) diseases by inhibiting the cell cycle and without disrupting neurogenesis (Liu et al. 2010), we now update and extend this strategy to applications in the treatment of cancers as well. Here, we put forth the concept of “aberrant cell cycle diseases” to include both cancer and CNS diseases, the two unrelated disease types on the surface, by focusing on a common mechanism in each aberrant cell cycle reentry. In this paper, we also summarize the pharmacological approaches that interfere with classical cell cycle molecules and mitogenic pathways to block the cell cycle of tumor cells (in treatment of cancer) as well as to block the cell cycle of neurons (in treatment of CNS diseases). Since cell cycle inhibition can also block proliferation of neural progenitor cells (NPCs) and thus impair brain neurogenesis leading to cognitive deficits, we propose that future strategies aimed at cell cycle inhibition in treatment of aberrant cell cycle diseases (i.e., cancers or CNS diseases) should be designed with consideration of the important side effects on normal neurogenesis and cognition.